Microencapsulation of Probiotic Strains by Lyophilization Is Efficient in Maintaining the Viability of Microorganisms and Modulation of Fecal Microbiota in Cats - Bruna M. Rodrigues; Paula M. Olivo; Milene P. Osmari; Ricardo S. Vasconcellos; Leonir B. Ribeiro; Ferenc I. Bankuti; Magali S. S. Pozza (International Journal of Microbiology)
High extrusion temperatures may compromise the functionality of probiotics in dry food. This study aimed to (i) evaluate the effects of two types of microencapsulation techniques, different encapsulating agents, and 120 days of storage on the viability of a commercial probiotic product and (ii) investigate fecal microbiota populations and fecal characteristics of adult cats fed with diets supplemented with probiotics. Three experimental treatments were evaluated: T1, commercial feed (control); T2, commercial kibbles coated with probiotics; and T3, commercial feed supplemented with freeze-dried probiotics and fructooligosaccharides. Fructooligosaccharides and gum arabic were used as encapsulating agents for freeze drying and spray drying and a pool containing Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus lactis, Bifidobacterium bifidum, Enterococcus faecium, and Saccharomyces cerevisiae as a probiotic. Diets were provided to 18 adult cats for 20 days. Feed samples were evaluated microbiologically, and feces were characterized according to their microbial content, pH, and fecal score. Freeze drying was more effective in maintaining microbial viability. Microcapsules prepared using fructooligosaccharides as encapsulants had the highest bacterial count: 8.74 log CFU/g of lactic acid bacteria and 8.75 log CFU/g of enterococci. Probiotics and synbiotics positively modulated (P<0.05) the fecal microbiota of cats, increasing the lactic acid bacteria counts from 3.65 to 4.87 and 5.07 log CFU/g, respectively. Microbial viability decreased significantly (P<0.05) after storage, demonstrating the need for effective protection mechanisms against extrinsic agents. In conclusion, the supplementation of cat diets with probiotics positively affected the gut microbiota. However, the results reinforce that probiotic microorganisms must be incorporated into the animal feed via effective mechanisms to withstand harsh processing conditions and storage.